Pengaruh Intensitas Aset Tetap, Thin Capitalization, dan Konservatisme Akuntansi Terhadap Tax Avoidance - Daffa Haykal Hakim; Aqamal Haq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to prove the effect of Fixed Asset Intensity, Thin Capitalization, and Accounting Conservatism on Tax Avoidance. The object of this research is companies included in the LQ-45 Index in 2020-2023. Sampling in this study using purposive sampling method. This research data was analyzed using panel data analysis with Eviews. The results in this study show the following findings: (1) Fixed Asset Intensity has a positive effect on Tax Avoidance, (2) Thin Capitalization has no effect on Tax Avoidance, (3) Accounting Conservatism has no effect on Tax Avoidance.